Homer2 and Alcohol: A Mutual Interaction - Castelli, Valentina; Brancato, Anna; Cavallaro, Angela; Lavanco, Gianluca; Cannizzaro, Carla (Frontiers in Psychiatry, 2017)
The past two decades of data derived from addicted individuals and preclinical animal models of addiction implicate a role for the excitatory glutamatergic transmission within the mesolimbic structures in alcoholism. The cellular localization of the glutamatergic receptor subtypes, as well as their signaling efficiency and function, are highly dependent upon discrete functional constituents of the postsynaptic density, including the Homer family of scaffolding proteins. The consequences of repeated alcohol administration on the expression of the Homer family proteins demonstrate a crucial and active role, particularly for the expression of Homer2 isoform, in regulating alcohol-induced behavioral and cellular neuroplasticity. The interaction between Homer2 and alcohol can be defined as a mutual relation: alcohol consumption enhances the expression of Homer2 protein isoform within the nucleus accumbens and the extended amygdala, cerebral areas where, in turn, Homer2 is able to mediate the development of the “pro-alcoholic” behavioral phenotype, as a consequence of the morpho-functional synaptic adaptations. Such findings are relevant for the detection of the strategic molecular components that prompt alcohol-induced functional and behavioral disarrangement as targets for future innovative treatment options.